Analysis of Lower Grade Students Gross Motor Ability Using Test of Gross Motor Development-2 (TGMD 2) Instrument - Erika Afriana; Martin Sudarmono (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Gross motor skills are an important foundation in supporting the physical development and participation of physical activity of elementary school-age children. This study aims to analyze the profile of locomotor ability, object control, and Gross Motor Quotient (GMQ) of elementary school students using the Test of Gross Motor Development-2 (TGMD-2) instrument. This study uses a quantitative approach with a descriptive design. The research subjects totaled 21 students aged 7–10 years who were selected using the total sampling technique. Data were obtained through the measurement of 12 basic motion skills consisting of six locomotor skills and six object control skills, then converted into standard values and GMQ based on TGMD-2 norms. Data analysis uses descriptive statistics including averages, standard deviations, percentages, and category distributions. The results showed that 80.95% of students were in the Average category and 19.04% were in the Below Average category with an average GMQ score of 93.71. These findings show that students' gross motor skills are generally in accordance with age-development norms, but a more varied and structured physical education learning strategy is needed to improve the quality of students' basic movement skills.